2019
DOI: 10.1111/jpn.13035
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐synthetic diet versus diet using natural ingredients—Comparative study in female Golden Syrian hamsters

Abstract: | INTRODUC TI ONLaboratory animals invariably serve as the basis for all scientific discoveries and technological advancements in the medical field including almost all medical knowledge, treatment regimes and medical device development. Proper selection of animal model for research is the key factor for extrapolation of animal research findings to humans, thus helping to improve the lives of people and other animals (Rand, 2008). Of the several factors that influence reproducibility of results, diet is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…More research is needed to confirm this hypothesis; only a limited number of studies have systematically compared breeding outcomes of rodents kept on semi-synthetic diet types to those of rodents kept on grain-based chow, and effects vary between studies. A recent study with Syrian hamsters showed that semi-synthetic diets can strongly reduce reproductive performance (36) whilst a different study, using rats, showed that birth weight was reduced as a result of semi-synthetic diet compared to grain-based diet (37), however, to our knowledge, impaired offspring survival has not been reported. Diet type did not appear to affect fertility, fetal implantation sites and litter size in CD-1 mice that were mated for 10 days (22).…”
Section: Breeding Outcomesmentioning
confidence: 75%
“…More research is needed to confirm this hypothesis; only a limited number of studies have systematically compared breeding outcomes of rodents kept on semi-synthetic diet types to those of rodents kept on grain-based chow, and effects vary between studies. A recent study with Syrian hamsters showed that semi-synthetic diets can strongly reduce reproductive performance (36) whilst a different study, using rats, showed that birth weight was reduced as a result of semi-synthetic diet compared to grain-based diet (37), however, to our knowledge, impaired offspring survival has not been reported. Diet type did not appear to affect fertility, fetal implantation sites and litter size in CD-1 mice that were mated for 10 days (22).…”
Section: Breeding Outcomesmentioning
confidence: 75%
“…More research is needed to confirm this hypothesis; only a limited number of studies have systematically compared breeding outcomes of rodents kept on semi-synthetic diet types to those of rodents kept on grain-based chow, and effects vary between studies. A recent study with Syrian hamsters showed that semi-synthetic diets can strongly reduce reproductive performance [ 36 ] whilst a different study, using rats, showed that birth weight was reduced as a result of semi-synthetic diet compared to grain-based diet [ 37 ], however, to our knowledge, impaired offspring survival has not been reported. Diet type did not appear to affect fertility, fetal implantation sites and litter size in CD-1 mice that were mated for 10 days [ 22 ].…”
Section: Discussionmentioning
confidence: 99%